الدرس التداولي بين الأصوليين وفلاسفة التحليل اللغوي (دراسة مقارنة - عيشوش, كنيوة, سندس سميرة; فضل, شريفة (جامعة الوادي university of eloued, 2018)
الملخص: إن التداولية هي دراسة اللغة أثناء الاستعمال, وقد جاءت نتيجة لأبحاث فلاسفة التحليل اللغوي أمثال أوستين وغرايس وسيرل, إذ أنتجوا منحى جديدا في تاريخ اللسانيات, من خلال ما توصلوا إليه فيما يخص الاستعمال والأفعال الكلامية والقصدية والاستلزام الحواري.... إلا أن ما جاؤوا به يعتبر موجودا في دراسات علم أصول الفقه, فالاستعمال موجود في مبحث الحقيقة والمجاز عند الأصوليين, والأفعال الكلامية التي جاء بها أوستين موجودة في مبحث الخبر والإنشاء, بينما القصدية فمتضمنة في مبحث المقاصد الأصولي, والاستلزام الحواري موجود في مبدأ التصديق والتبادر والإعمال الأصوليين. وهذا يبرز مدى إلمام تراثنا العربي الأصولي بكل ما يبدو معاصرا وجديدا, لذلك فهو يستحق الكثير من الدراسات التأصيلية لتنفض الغبار عنه. Abstract The Pragmatism is the study of language during use, and was the result of the research philosophers of linguistic analysis such as Austin, Grays and Searl, they produced a new trend in the history of linguistics, through what they have reached in terms of use and verbal and intentional actions and dialogue invocation However, what they came to is considered in the studies of the doctrine of jurisprudence, the use exists in the study of truth and metaphor of the fundamentalists, and the verbal acts that came to Austin found in the subject of news and construction, while the intention included in the study of the purposes of fundamentalism, and the invocation of dialogue is in the principle of ratification and departure and implementation Fundamentalists. This highlights the extent to which our Arab heritage is familiar with everything that seems modern and new, so it deserves a lot of ground-breaking studies to shake it off.
Keywords: التداولية، الأصوليون، فلاسفة التحليل اللغوي; Pragmatism, fundamentalists, linguistics philosophers